Spiroxys contortus (Rudolphi, 1819) and Hedruris orestiae (Moniez, 1889) in Argentine turtles - Palumbo, Ezequiel (2016)
Knowledge of parasites in turtles is scarce,particularly with regard to freshwater turtles of SouthAmerica. Here, we describe the association of Spiroxyscontortus (Rudolphi, 1819) in Phrynops hilarii (Duméril& Bibron, 1835) and S. contortus and Hedruris orestiae(Moniez, 1889) in Hydromedusa tectifera (Cope, 1870).The presence of S. contortus in P. hilarii represents anew host record and also the southernmost geographicrecord for this species. More interestingly, the presenceof H. orestiae in H. tectifera represents the first record ofthis helminth species from a reptilian host.